Cooperative Script Berdiferensiasi untuk Meningkatkan Membaca Kritis Teks Editorial Siswa SMA - Wira Manik; Asnita Hasibuan; Candra Ronitua Gultom; Samserida Sarumpaet (Pustaka Karya Mandiri, 2026)
Critical reading ability is a high-level literacy competence that is essential for senior high school students to distinguish facts, opinions, and underlying biases in editorial texts. This study aims to improve the critical reading skills of eleventh-grade students at SMA Nurcahaya in editorial text learning through the Cooperative Script model based on process-differentiated instruction. This study employed Classroom Action Research conducted in two cycles, with each cycle consisting of planning, action, observation, and reflection. The subjects were 36 eleventh-grade students at SMA Nurcahaya. Data were collected using critical reading performance tests covering fact-opinion analysis, inference making, bias evaluation, and reconstruction of authorial perspectives, as well as observation sheets for student and teacher activities. The data were analyzed using descriptive quantitative and qualitative techniques. The findings revealed gradual improvements in both learning process quality and student achievement. In the pre-cycle phase, the class average score was 64.12 with classical completeness of 33.33%. After Cycle I, the mean score increased to 73.45 with classical completeness of 61.11%. In Cycle II, through refined grouping based on readiness and varied scaffolding, the mean score rose to 82.78 with classical completeness of 88.89%. These findings indicate that integrating Cooperative Script and process differentiation effectively improves students critical reading ability, reduces reading fatigue, and accommodates heterogeneous learning modalities and paces.